Fenugreek Galactomannan and Its Versatile Applications - Vanya Nalbantova; Niko Benbassat; Cédric Delattre (Polysaccharides, 2024)
Fenugreek (Trigonella foenum-graecum L.) is an annual, dicotyledonous medicinal plant which belongs to the Leguminosae family, and its leaves and seeds are widely used and cultivated throughout the world. Their widespread utilization is attributed to the great variety of primary and secondary metabolites they contain, such as flavonoids, alkaloids, steroidal saponins, tannins, as well as carbohydrates, in particular galactomannan, which is the focus of the current study. The presence of an equal number of galactose and mannose residues (Gal/Man ratio of 1:1) prevents the formation of hydrogen bonds between the mannose ones. This determines the good solubility of fenugreek galactomannan in cold water, even at low concentrations. The water solubility would be significantly better than that of carob and even slightly higher than that of guar gum, precisely due to their structural characteristics, which contribute to their possible advantages. Moreover, it is a good alternative as an excipient for the development of pharmaceutical dosage forms, as well as in the preparation of food products, affecting not only their structure but also their shelf life. Furthermore, it has promising applications not only in the fields of medicine and pharmaceutics but also offers environmental benefits. All of the above-mentioned factors are of high interest and qualify fenugreek galactomannan as a versatile polysaccharide, which is the reason for summarizing its benefits in this review.